2017
DOI: 10.1073/pnas.1620982114
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Gentamicin B1 is a minor gentamicin component with major nonsense mutation suppression activity

Abstract: Nonsense mutations underlie about 10% of rare genetic disease cases. They introduce a premature termination codon (PTC) and prevent the formation of full-length protein. Pharmaceutical gentamicin, a mixture of several related aminoglycosides, is a frequently used antibiotic in humans that can induce PTC readthrough and suppress nonsense mutations at high concentrations. However, testing of gentamicin in clinical trials has shown that safe doses of this drug produce weak and variable readthrough activity that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
2
37
2
Order By: Relevance
“…We previously reported that the major components of pharmaceutical gentamicin showed only weak PTC readthrough activity (8), corroborated recently by Friesen (9), but that the minor component B1was a potent readthrough compound (8). Here, we correct the record and show that the B1 used in our study was misidentified by the vendor and was in fact G418, and we provide evidence that synthetic gentamicin B1 is inactive as a readthrough compound.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We previously reported that the major components of pharmaceutical gentamicin showed only weak PTC readthrough activity (8), corroborated recently by Friesen (9), but that the minor component B1was a potent readthrough compound (8). Here, we correct the record and show that the B1 used in our study was misidentified by the vendor and was in fact G418, and we provide evidence that synthetic gentamicin B1 is inactive as a readthrough compound.…”
Section: Discussionsupporting
confidence: 83%
“…We found that none of the major gentamicins showed significant activity, an observation recently corroborated by others (9). We reported that the minor component gentamicin B1 was 30-to 100fold more potent than the most potent gentamicin batches tested (8). In recent structure-activity relationship studies to be reported elsewhere, we observed that synthetic aminoglycoside analogs bearing ring 1 of gentamicin B1 lacked readthrough activity whereas analogs bearing ring 1 of the closely related aminoglycoside G418 showed readthrough activity.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…EC 50 values found in intact cells differ considerably from those measured by our cosedimentation assay, being much higher for AGs, 23,30 and much lower for ataluren, 8,31 RTC13 25 and GJ072. 25 We attribute these differences to the poor uptake of positively charged aminoglycosides into cells, while uptake is favored for the hydrophobic ataluren-like molecules.…”
Section: Coo -contrasting
confidence: 80%